HARNESSING TECHNOLOGY: EVALUATING MOBILE PHONE TEXT MESSAGING AS A DIABETES SUPPORT INTERVENTION - Mitchell , Katherine E.; Thompson, Samuel J. (Research Journal of Health, Medicine and Nursing, 2024)
Diabetes Mellitus (DM) is a pervasive and enduring global health concern, contributing significantly to mortality, morbidity, and substantial healthcare resource utilization (World Health Organization, 2020). The escalating incidence of DM poses unprecedented challenges to healthcare systems worldwide, necessitating a strategic focus on enhancing diabetes care and patient outcomes through self-management interventions (Lin et al., 2020; Kitsiou et al., 2017; Powers et al., 2017). This paper explores the chronic nature of DM, arising from pancreatic insufficiency or impaired insulin utilization, leading to persistent hyperglycemia and consequential organ damage. The repercussions include vision loss (retinopathy), renal failure (neuropathy), and neurological disorders (Liu et al., 2020; Lotfy et al., 2017). To address the burgeoning prevalence and impact of DM, it is imperative for healthcare providers and policymakers to adopt effective self-management interventions. These interventions play a pivotal role in mitigating the enduring effects of DM, thereby improving patient outcomes and alleviating the strain on healthcare systems. The objective of this paper is to critically examine the current landscape of diabetes care and the role of self-management interventions in optimizing patient well-being. The relentless rise in DM cases underscores the urgency for a comprehensive approach to diabetes management. The paper reviews existing literature on the subject, synthesizing evidence from studies conducted by Lin et al. (2020), Kitsiou et al. (2017), Powers et al. (2017), Liu et al. (2020), Lotfy et al. (2017), and others. By analyzing these studies, the paper aims to identify key trends, challenges, and opportunities in diabetes care, with a specific focus on the impact of self-management interventions.